APPLICATION OF DIGITAL IMAGE CORRELATION TO CAPTURE THE CRACK MOUTH OPENING DISPLACEMENT OF THE NOTCHED STEEL FIBER REINFORCED CONCRETE (SFRC) BEAM - Mudji Irmawan; Bambang Piscesa; Priyo Suprobo; Harun Alrasyid (Journal of Civil Engineering, 2022)
The application of digital image correlation (DIC) to capture any point in the experimental test is found to be promising. Using the DIC and appropriate tool can overcome the limitation of the traditional sensors to capture the movement or displacement in the tested specimen. In this study, an open-source DIC called Digital Image Correlation Engine (DICE) is used to capture the crack mouth opening displacement (CMOD) of the notched steel fiber reinforced concrete (SFRC) beam with points tracking method. There are three beam specimens with different sizes and similar aspect ratios reported in this paper. All beams have 0.5% steel fiber volumetric content. The SFRC beams are marked with points and tested under a three-point bending flexural test. Custom firmware for Canon DSLR 650D digital camera called Magic Lantern is used to capture the pictures per one second. DICE software is used to analyze the point movements and dumped the output file. ParaView 5.9.0 is then used to visualize the data. A method to calibrate the point coordinate with actual measurement is proposed. A small script is written in Visual Basic Application (VBA) in Microsoft Excel to correlate the displacement for each point of interest with the recorded applied load. With the developed script, any point of interest tracked with DICE can be related to the recorded data from the data logger. From this study, the obtained CMOD with the corresponding applied load is presented, which can be used to investigate the flexural fracture energy of the SFRC beam.